DEFINITION OF THE MAIN PHENOMENONS OF SELF-CONSCIOUSNESS OF THE PERSONALITY - Biletskiy, Alexey (PSYCHOLOGICAL JOURNAL, 2017)
The article is sanctified to the study of the last researches of the basic phenomena of self-consciousness, exposing the mechanisms of their realization and hierarchy of influence on development of personality. In the work it is established that a leading role in constructing of new-style of life and transformation of the inner world of personality modern psychology justly takes to strengthening of processes related to such phenomena of self-consciousness, as self-knowledge, self-relation and self-regulation. Life in the collective gradually accustomed people to think about their thoughts and actions before acting and talking, to take into account the possible consequences of the opinions expressed and actions taken. Therefore, the appeal to inner peace and inner life of a person is the key moment in understanding man himself. Self-knowledge is this study by personality of own psychical and physical features, comprehension itself. Self-relation is a specific type of the emotional experiencing, in that own attitude of personality is reflected toward that she knows, understands, and opens in relation to itself. It should be noted that the results of integrative work in the field of self-knowledge, on the one hand, and in the sphere of the emotional-value relation to oneself (self-relation), on the other, unite into a special phenomenon of self-consciousness of the personality – its self-evaluation. At the same time, the phenomenon of self-regulation should be considered relying on the two-level structure of the I-Concept, where the first level is defined within the framework of the innate human potential, and the second level of the I-Concept is that which forms in a person in the process of socialization and becomes stable in adolescence. This psychological model of the I-Concept, as a product of self-consciousness, allows us to define self-regulation as a cyclic process of constant actualization and realization by the personality of its innate potential. Where self-realization is the process of unfolding the properties and characteristics of a person that are contained at the first level of the I-Concept, into the second level of the I-Concept. And self-realization is a process of personal development and broadcasting by the personality of her content to other people and culture through the I-Concept of the second level. The results of recent studies of the main phenomena of self-consciousness point to the need to define more concrete content of such concepts as self-actualization and self-realization, as well as to identify new mechanisms of self-consciousness that will contribute to a better self-development of the personality.